Survey of dental graduates who have not received government employment in Sri Lanka - De Silva, M.D.K (My University, 1999)
Descriptive cross sectional study was carried out to document socio demographic characteristics, present employment pattern and expectations towards government employment. 71 percent were engaged in private practice. Universities and defense forces were the other main sources of employment. A dental surgeon's monthly income had a median value of Rs. 13,000/=. Forty four percent of dental surgeons were concentrated in Colombo district. There was no relationship between the district of entrance to the university and the district of practice. Only 10 per cent practiced hi- tec procedures such as dental bridges. Almost all preferred to have a compulsory internship and government employment. At present non availability of government employment is not a serious problem as the majority are gainfully employed as private practitioners. But it will be a serious problem within next 3 years. Restriction of intake of dental students to the university, introduction of a compulsory internship and provision of incentives to those who wish to establish practices in rural areas need to be considered.